Ethanol recovery section a design report - Lu, Caroline T.; Lucas, Jesus R. Jr.; Manalo, Julius L. (Diliman, Quezon City College of Engineering, 1982)
Capacity (pretreatment and ethanol): 122.82 MT/day ethanol, 43.78 MT/day furfural, 103.50 MT/day lignin -- Total capital investment: P 290.78 M -- Total annual sales at 100% capacity: P 189.33 M -- Total annual product cost: P 117.59 M -- Annual profit before taxes at 100% capacity: P 71.74 M -- - Annual profit ftera taxes at 100% capacity: P 37.30 M -- Land area (pretreatment and ethanol): 47,720 sq. meters -- Ethanol plant size: 3,000 sq. meters -- Site: Bislig, Surigao del Sur, Philippines -- Projected life span: 20 years
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Ethanol